Human Resource Management Dalam Meningkatkan Mutu Dosen PTKIS - Fauzi, Ahmad (At- Ta'lim : Jurnal Pendidikan, 2018)
The existence of Islamic education today, facing various problems ranging from the foundational and operational, and can not be resolved properly. This condition certainly draws a lot of attention among practitioners and managers of Islamic education to be neatly disentangled and can be found the tip of the base. The various problems, in the background by the government's policy on the higher education system by applying at least every course of study, must have six lecturers in accordance with their area of expertise, coupled with the urge to immediately transfer status. This condition on the one hand will have a positive and negative impact. Therefore, this paper briefly aims to parse the problem, through the approach of human resource management for Islamic higher education in improving the quality of human resources. Due to the quality of human resources, it can significantly impact the institutional management system and graduate quality especially for PTKI. Management of human resources is the most important aspect in the management system, therefore the function of MSDM must be optimally implemented in accordance with the needs and objectives of the organization to give birth to the quality of Islamic higher education. In addition, the management of human resources is expected to pay attention to the recruitment process recruitment and open competition, through planning, organizing, implementing and evaluating, so as to give birth to the quality of PTKI ready to compete in the midst of globalization era. Keywords; human resource management, and the quality of PTKIS lecturers